“Ain’t I Got a Right to the Tree of Life?”: Examining Special Education through the Application of Afro-Humanity - Banks, Joy; Shockley, Kmt; Wilkerson, Courtney (Philosophical Inquiry in Education)

(untitled) (Canadian Philosophy of Education Society, 2021)
In this manuscript we chart the intersection of dis/ability and Afro-humanity. We propose that Afro-humanity is a contextual paradigm within African-centred ideology that can be applied to explore the ways in which disability may be perceived differently when applying a specific, cultural philosophical lens. We also explore the process of decolonization, whereby African American parents, with a child identified with an intellectual disability, reorient themselves to a way of thinking that is more emancipatory. The parents act in a way that challenge concepts about human cognitive variance and notions of dis/ability in school settings. Drawing on such a model as Afro-humanity, we argue for a more equitable approach to community and educational engagement for Black students labelled with dis/abilities.